2020
DOI: 10.17576/geo-2020-1604-01
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the local community toward the yellow-crested cockatoo (Cacatua sulphurea abbotti), a critically endangered species in Masakambing Island, Indonesia

Abstract: The yellow-crested cockatoo is an endangered species with habitat is in a non-conservation area with community ownership. The local community's action is determined by perception related to the information about this animal. The study aimed to find out the perception of the local community of Masakambing Island to the yellow-crested cockatoo based on community structure and the advantages-disadvantages aspect. The study was conducted in Masakambing Island, Masalembu sub-district, Sumenep Regency, East Java Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Then, it is followed by Mandarese of West Sulawesi. The Madurese arrived late in the 1940s, as Ihsannudin et al (2020) found that the Madurese who came to the Masalembu islands, including the inhabitants of Masakambing island, departed from the ports of Nepa and Ketapang on the north coast of Madura and from the Sumenep.…”
Section: • the History Of Masakambing Islandmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, it is followed by Mandarese of West Sulawesi. The Madurese arrived late in the 1940s, as Ihsannudin et al (2020) found that the Madurese who came to the Masalembu islands, including the inhabitants of Masakambing island, departed from the ports of Nepa and Ketapang on the north coast of Madura and from the Sumenep.…”
Section: • the History Of Masakambing Islandmentioning
confidence: 99%
“…It coversan area of 7.79 square kilometers and is administratively part of Masakambing Village, Masalembu District, Sumenep Regency, East Java Province. The people who inhabit this island are mostly dominated by Buginese, besides Mandarese and Madurese as well (Ihsannudin et al, 2020). A small island with a multiethnic community is also found in Sabah, East Malaysia (Majid Cooke & Johari, 2019).…”
Section: Introductionmentioning
confidence: 99%